2021
DOI: 10.48550/arxiv.2103.01976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superdiffusion in spin chains

Vir B. Bulchandani,
Sarang Gopalakrishnan,
Enej Ilievski

Abstract: This review summarizes recent advances in our understanding of anomalous transport in spin chains, viewed through the lens of integrability. Numerical advances, based on tensor-network methods, have shown that transport in many canonical integrable spin chains-most famously the Heisenberg model-is anomalous. Concurrently, the framework of generalized hydrodynamics has been extended to explain some of the mechanisms underlying anomalous transport. We present what is currently understood about these mechanisms, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 213 publications
(440 reference statements)
7
28
1
Order By: Relevance
“…Using Generalized Hydrodynamics (GHD) [39,40] (see also Refs. [41][42][43][44][45][46]) we analytically tackle transport within the isolated magnon sector. Since the Alcaraz-Bariev (AB) model is a close relative of the XXZ spin chain, it inherits its rich phenomenology: transport greatly depends on the interactions and can exhibit sharp jumps [47].…”
mentioning
confidence: 99%
“…Using Generalized Hydrodynamics (GHD) [39,40] (see also Refs. [41][42][43][44][45][46]) we analytically tackle transport within the isolated magnon sector. Since the Alcaraz-Bariev (AB) model is a close relative of the XXZ spin chain, it inherits its rich phenomenology: transport greatly depends on the interactions and can exhibit sharp jumps [47].…”
mentioning
confidence: 99%
“…On the one hand, in the case of the quantum chain, this superdiffusive behavior is by now well established at the isotropic point (see Ref. 19 and references therein). On the other hand, in the case of the classical chain, the nature of spin transport at the isotropic point has been quite controversial [33][34][35][36][37][38][39] .…”
Section: D Chainmentioning
confidence: 80%
“…Moreover, plotted in a double-logarithmic representation [Fig. 1 (b)], we find that the hydrodynamic power-law tail C (M) (t) ∝ t −α at intermediate times is well described by α ≈ 2/3, which suggests superdiffusive transport within the Kardar-Parisi-Zhang (KPZ) universality class 18,19,57,59,62,63 (for more details see Sec. IV A 1 below).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…When a system is showing spatiotemporal chaos (STC), i.e., chaos characterized by spatial and temporal disorder, perturbations given to trajectories typically grow exponentially and fluctuate. Pioneering studies by Pikovsky, Kurths, and Politi [10,11] revealed that, for a wide range of systems, this growing perturbation belongs to the Kardar-Parisi-Zhang (KPZ) universality class [12], which is one of the most wide-ranging universality classes for various stochastic processes (see reviews [13][14][15][16][17][18][19]), including growing interfaces, directed polymers, stochastic particle transport, nonlinear fluctuating hydrodynamics [18,20], and most recently, to quantum spin chains [21][22][23][24], to name but a few.…”
mentioning
confidence: 99%